2018
DOI: 10.3389/fgene.2018.00169
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing Revealed a CpG Methylation Pattern Associated With ALDH1L1 Suppression in Breast Cancer

Abstract: Hypermethylation of promoter CpG islands is generally recognized epigenetic mechanism responsible for gene silencing in cancer. However, molecular details on how this epigenetic mark triggers the process of gene downregulation are still elusive. Here, we used deep bisulfite sequencing and qPCR analysis to investigate the pattern of CpG methylation of ALDH1L1 promoter region and its association with the gene expression level in 16 paired breast cancer (BC) samples of different clinical stages. Expression of ALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…DNA methylation of promoter-associated CpG islands can function as a potential mechanism of silencing tumor suppressor genes in numerous cancers, including HCC [ 39 ]. Hypermethylation of CpG islands in the promoter region of tumor suppressor genes is a major event in the development of many cancers [ 40 ]. MKP-4 also acts as a tumor suppressor gene in many other cancers in addition to HCC and it has been reported that promoter methylation of DUSP9 in human gastric cancer and colorectal cancer is an important reason for its decreased expression [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation of promoter-associated CpG islands can function as a potential mechanism of silencing tumor suppressor genes in numerous cancers, including HCC [ 39 ]. Hypermethylation of CpG islands in the promoter region of tumor suppressor genes is a major event in the development of many cancers [ 40 ]. MKP-4 also acts as a tumor suppressor gene in many other cancers in addition to HCC and it has been reported that promoter methylation of DUSP9 in human gastric cancer and colorectal cancer is an important reason for its decreased expression [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in strict contrast to other folate enzymes, which are commonly up-regulated in cancer (Jain et al, 2012; Ducker and Rabinowitz, 2017). Several studies have established that the silencing of ALDH1L1 in human cancers is driven by gene methylation (Oleinik et al, 2011; Dmitriev et al, 2012; Senchenko et al, 2013; Dmitriev et al, 2014; Beniaminov et al, 2018). Methylation takes place in the CpG island, which includes 96 CpG base pairs and covers the promoter, first exon and the part of the first intron in ALDH1L1 (Oleinik et al, 2011; Beniaminov et al, 2018).…”
Section: Evidence That Aldh1l1 Is a Candidate Tumor Suppressormentioning
confidence: 99%
“…Several studies have established that the silencing of ALDH1L1 in human cancers is driven by gene methylation (Oleinik et al, 2011; Dmitriev et al, 2012; Senchenko et al, 2013; Dmitriev et al, 2014; Beniaminov et al, 2018). Methylation takes place in the CpG island, which includes 96 CpG base pairs and covers the promoter, first exon and the part of the first intron in ALDH1L1 (Oleinik et al, 2011; Beniaminov et al, 2018). Remarkably, a microarray-based global gene expression profiling of approximately 42,000 genes has found that ALDH1L1 was one of the most down-regulated proteins in primary hepatocellular carcinomas and in liver metastases (Tackels-Horne et al, 2001).…”
Section: Evidence That Aldh1l1 Is a Candidate Tumor Suppressormentioning
confidence: 99%
“…In addition, ALDH1L1 is considered as a potential biomarker for poor prognosis of gastric cancer 31 . ALDH1L1 expression is inhibited in BC patients, and the mean hypermethylation level in the promoter region was positively correlated with the down-regulation of ALDH1L1 32 . In addition, high expression of ALDH1L1 is found to be associated with better overall survival in BC patients 33 .…”
Section: Discussionmentioning
confidence: 96%